Peningkatan Partisipasi Belajar IPA Melalui Penerapan Strategi Pembelajaran Word Square Pada Kelas IV SD Muhammmadiyah 11 Mangkuyudan Surakarta Tahun Ajaran 2015/2016 - SETIAWAN, DODI (2016)
ABSTRACT This study aims to increase the participation of students of class IV SD Muhammadiyah Surakarta 11 Mangkuyudan through learning strategies word square. The subjects of this study were teachers and fourth grade students of SD Muhammadiyah 11 Mangkuyudan Surakarta. The procedure of this study conducted two cycles consisting of four stages: planning, action, observation and reflection. Techniques of data collection is done through observation, interviews, tests and documentation. Data analysis technique conducted by Data Reduction, Presentation of Data, Data Verification, Withdrawal conclusion. Results showed Increased Participation of Learning students as follows: in the first cycle Giving opinions to solving a number of 26 or 66%, provide feedback to the opinions of others some 26 or 66%, Working tasks assigned by the teacher some 53 or 64%, Has responsibility responsibility as a member of a group of up to 27 or 69%, and Working-class problems in front of a number of 29 or 74%. while in the second cycle Giving opinions to solving a number of 33 or 84%, provide feedback to the opinions of others were 34 or 87%, Working tasks assigned by the teacher some 33 or 84%, Has a responsibility as members of some 36 or 92% and Working problems in front of the class number of 35 or 89%. From this study it can be concluded through the application of learning models Word Square can increase the participation of students of class IV SD Muhammadiyah Surakarta 11 Mangkuyudan year 2015/2016. Keywords: Word Square, Participation Learning, Science, Learning Outcomes.